New forms of the Lopatynsky condition - Il’kiv, V. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.956.223+512.64We present known forms of the Lopatynsky condition of ellipticity of a problem for a linear regularly elliptic system of equations and determine new forms of this condition.Several examples of its application to various elliptic systems of equations are considered.